Investigating the effect of habitat modification on chronic stress in deer mice: a preliminary study - Eleftheriou, Andreas; Luis, Angela D. (Wildlife Rehabilitation Bulletin, 2021)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Anthropogenic habitat modification can lead to chronic stress in wildlife. This can result in immunosuppression and higher disease prevalence. Chronically stressed individuals typically have elevated baseline GCs and decreased body condition. GCs are called FGMs when excreted in feces and can be used to noninvasively evaluate stress in free-ranging wildlife. In the deer mouse (<em style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Peromyscus maniculatus<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">)–SNV system, SNV prevalence is higher in deer mice at peridomestic settings, which are human-modified habitats. This is problematic because SNV causes a fatal disease in humans, and thus the higher SNV prevalence may lead to higher risk of infection for humans. In our study, we hypothesized that SNV prevalence would be higher in deer mice at human-modified habitats due to chronic stress. To test our hypothesis, we compared two stress measures (i.e., baseline FGMs and body condition scores) in deer mice from one peridomestic and one sylvan grid over 2 months. Captured deer mice were tagged, weighed, sexed and sampled for feces and blood and were evaluated for reproductive status and body condition before release. Blood samples were analysed for SNV antibodies, and fecal samples were evaluated for FGMs. We found higher deer mouse numbers at the sylvan grid. There were no differences in baseline FGM levels between peridomestic and sylvan populations. However, peridomestic deer mice had overall lower body condition. Given the low SNV prevalence across both grids, we were unable to examine potential correlations between SNV prevalence and chronic stress. Regardless, we conclude that deer mice at human-modified habitats may not be chronically stressed, which may suggest that higher SNV prevalence at peridomestic settings may not be the result of chronic stress. Although we did find that peridomestic deer mice had lower body condition, this may not have been related to chronic stress because there were no differences in baseline FGMs. Longer studies with more site replication are needed to validate and expand on our findings. Our preliminary study adds to the existing body of knowledge that examines relationships between stress physiology and disease prevalence in human-modified environments.